Quality Of Work Life dan Perilaku Cyberloafing Pada Karyawan - Patmawati, Patmawati (Psycho Aksara : Jurnal Psikologi, 2023)
Cyberloafing behavior is the activity of using company internet access for personal gain which is carried out when employees are still working (during working hours); so, that this cyberloafing behavior Will affect the work productivity of the employee concerned. The factors that influence the emergence of cyberloafing behavior is individual, situasional anda organizational factors. Employees are vulnerable to work stress experienced by employees who have a low quality of work life, and organizational control (organizational factors) also effect the quality of work life in employee. Therefore is necessary to examine the relationship between the quality of work life of employees and cyberloafing behavior. The research subjects are employees who work at CV. X and have acces to ise the office internet, namely 94 people. The research hypothesis is that there is a negative relationship between quality of work life and cyberloafing behavior, where the higher the quality of employee work life, the lower of cyberloafing behavior. Data collection uses a quality of work life scale based on Cascio's theory (2003) and cyberloafing behavior scale based on Lim's theory (2002). Data analysis using the Perason Parametrical Statisticsl Test showe result = -0,302 and p = 0,049 (0,05).